2009
DOI: 10.1002/cbic.200900054
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Sequencing of the Biosynthetic Gene Cluster for Saquayamycin Z and Galtamycin B and the Elucidation of the Assembly of Their Saccharide Chains

Abstract: Sweet ways: We have investigated the glycosyltransferase genes of the saquayamycin Z (shown) and galtamycin B biosynthetic gene cluster from Micromonospora sp. Tü6368. The results unambiguously show that both compounds are derived from the same cluster. Furthermore, the function of five glycosyltransferases was elucidated, and the results have shed light on the assembly of the sugar chains.The Gram-positive bacterium, Micromonospora sp. Tü6368 produces the angucyclic antibiotic saquayamycin Z and the tetracene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 32 publications
1
51
0
Order By: Relevance
“…KCTC 11604BP [32] and fkbN is present in all other identified FK506 gene clusters [30]. We introduced fkbN into S. coelicolor M1146/PAC20N#3 using the replicative, conjugative expression plasmid pUWL- oriT - apr containing the strong constitutive ermE * promoter [44] and monitored FK506 production levels as above. While growth rates and biomass accumulation were comparable, over-expression of fkbN resulted in approximately five-fold FK506 yield improvements (5.5 mg L −1 compared to 1.2 mg L −1 observed upon introduction of an empty pUWL- oriT - apr plasmid; Figure 4B), demonstrating that fkbN over-expression is also beneficial to FK506 yields when the cluster is expressed heterologously.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KCTC 11604BP [32] and fkbN is present in all other identified FK506 gene clusters [30]. We introduced fkbN into S. coelicolor M1146/PAC20N#3 using the replicative, conjugative expression plasmid pUWL- oriT - apr containing the strong constitutive ermE * promoter [44] and monitored FK506 production levels as above. While growth rates and biomass accumulation were comparable, over-expression of fkbN resulted in approximately five-fold FK506 yield improvements (5.5 mg L −1 compared to 1.2 mg L −1 observed upon introduction of an empty pUWL- oriT - apr plasmid; Figure 4B), demonstrating that fkbN over-expression is also beneficial to FK506 yields when the cluster is expressed heterologously.…”
Section: Resultsmentioning
confidence: 99%
“…The genes encoding the FK506 regulators FkbN and FkbR were PCR amplified from the FK506 PAC and ligated independently into separate pUWL- oriT-apr vectors containing the ermE * promoter [44], [53]. The forward primer for each amplicon (Table 1) contained a Streptomyces ribosome binding site [54].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, as is the case for ActR, at least one step in the induction of the LanK target operon involves the interaction of the repressor with an immature landomycin intermediate. TFRs are also located in the biosynthesis clusters for the related angucyclinone antibiotics urdamycin and saquayamycin, but the role of these TFRs in regulating antibiotic biosynthesis and export has not been investigated (83,84).…”
Section: Tfrs Regulating Self-resistance In Antibiotic-producing Orgamentioning
confidence: 99%
“…Based on the structures of the putative intermediates, it was suggested that the carbon scaffold of 69 maybe formed through fusing one molecule of malonic acid to an angucycline intermediate 88. The natural host of saquayamycin Z 70 is reported to produce the linear polyketide galtamycin B 71 89. However, inactivation of glycosyltransferase saq GT5 or saq GT6 in the gene cluster of 70 eliminated the synthesis of 71 , which suggested the biosynthesis of 70 and 71 are related and may both be derived from 57 .…”
Section: Cyclization Of Bacterial Aromatic Polyketidesmentioning
confidence: 99%